Circuit Design on Plastic Foils - Raiteri, Daniele; Cantatore, Eugenio; van Roermund, Arthur; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book illustrates a variety of circuit designs on plastic foils and provides all the information needed to undertake successful designs in large-area electronics.  The authors demonstrate architectural, circuit, layout, and device solutions and explain the reasons and the creative process behind each. Readers will learn how to keep under control large-area technologies and achieve robust, reliable circuit designs that can face the challenges imposed by low-cost low-temperature high-throughput manufacturing.   • Discusses implications of problems associated with large-area electronics and compares them to standard silicon; • Provides the basis for understanding physics and modeling of disordered material; • Includes guidelines to quickly setup the basic CAD tools enabling efficient and reliable designs; • Illustrates practical solutions to cope with hard/soft faults, variability, mismatch, aging and bias stress at architecture, circuit, layout, and device levels.
Introduction -- Applications of large-area electronics on foils -- State of the art in circuit design -- Device modeling and characterization -- Sensor frontend architecture -- Circuit design for analog signal conditioning -- Circuit design for data conversion -- Circuit design for digital processing -- Conclusions.
Keywords: Electronic circuits; Electronics; Microelectronics; Circuits and Systems; Electronic Circuits and Devices; Electronics and Microelectronics, Instrumentation